Evaluation of teaching methods for students on hernias: an observational study. (26th September 2012) - Peacock, Oliver; Watts, Edward; Foreman, David; Lund, Jonathan N.; Tierney, Gillian M.
Abstract: Background: Teaching may be delivered through different media in different settings. We aimed to evaluate four teaching modalities for medical students on a common surgical topic. We compared learning, student preferences and experiences as outcome measures. Methods: This is a prospective observational study of all medical students undertaking their first attachment in surgery. Students were randomly allocated into four groups: lecture, handout, website and patient‐based tutorial, all on the management of an inguinal hernia. Baseline knowledge was assessed prior to group allocations through a questionnaire. Students completed a 24‐h post‐intervention questionnaire and satisfaction survey. Results: One hundred fifty‐four students participated. There was no difference in the pre‐intervention knowledge scores between the groups. The post‐intervention knowledge scores significantly improved in the lecture and website groups. However, the website was significantly less engaging and clinically relevant form of teaching compared with the lecture. Despite being engaging and relevant, the tutorial group failed to improve knowledge scores. The handout did not improve knowledge scores, nor was it considered engaging or relevant. Conclusion: Knowledge scores significantly improved with the lecture and website teaching methods. The lecture was more engaging, clinically relevant and instilled confidence. Students preferred the website/podcasts as additional information to facilitate their learning and increased their knowledge equivalent or superior to other standard media. However, despite being effective, the student experience was less positive than for non‐reusable contact teaching. If student satisfaction is to be a factor in achievement of learning outcomes, a balance has to be struck between different media delivery.